1987
DOI: 10.1111/j.1834-7819.1987.tb01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Provisional coronal build‐up of posterior teeth for endodontic treatment. Case report

Abstract: A technique using a glass-cermet cement for preendodontic coronal build-up of badly broken-down teeth is described. This glasscermet cement fulfils the more specific requirements of a material used in coronal build-ups of a less permanent nature without damage to existing tooth structure and satisfies the requirements of endodontic procedures. The technique allows for endodontic therapy to be commenced immediately and facilitates canal instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…IRM was assessed and compared to other temporary restorative materials in a number of studies both in vivo and in vitro with con£icting ¢ndings. In an in vivo study, IRM performed almost equally to Cavit for temporizing class I access cavities in human teeth using a 4-mm thickness over a 3-week period (Beach et al 1996). In an in vitro study, IRM allowed to set next to CMCP prevented Proteus vulgaris penetration signi¢cantly better than Cavit set next to both CMCPand saline solution (Blaney et al1981).…”
Section: Zinc Oxide and Eugenol Preparationsmentioning
confidence: 87%
See 4 more Smart Citations
“…IRM was assessed and compared to other temporary restorative materials in a number of studies both in vivo and in vitro with con£icting ¢ndings. In an in vivo study, IRM performed almost equally to Cavit for temporizing class I access cavities in human teeth using a 4-mm thickness over a 3-week period (Beach et al 1996). In an in vitro study, IRM allowed to set next to CMCP prevented Proteus vulgaris penetration signi¢cantly better than Cavit set next to both CMCPand saline solution (Blaney et al1981).…”
Section: Zinc Oxide and Eugenol Preparationsmentioning
confidence: 87%
“…In another study, Melton et al (1990) found that TERM provided 67% sealability compared to 100% for Cavit when used to seal-etched and nonetched cavities without thermocycling. In vivo, it was found that TERM is inferior to IRM and Cavit in class I cavities when used in 4-mm thickness and for a 3-week temporization period (Beach et al 1996). Many other studies have demonstrated similar e¡ectiveness of TERM and Cavit.…”
Section: Glass-ionomer Cementmentioning
confidence: 97%
See 3 more Smart Citations